Forced online and distance learning during COVID-19 pandemic: students’ perceptions and experiences / Mohd Izani Othman ... [et al.] - Othman, Mohd Izani; Sulaiman, Suraya; Mohd Najib, Mohd Nadzri; Wan Ismail, Wan Nordini Hasnor (Universiti Teknologi MARA, 2022)
The emergence of COVID-19 pandemic has forced educational institutions to change and adapt to ODL. This is to avoid disruption to students’ education and study plans. However, the forced actions resulted in mixed reactions from students and educators. Both parties were not ready and anticipated difficulties in executing forced ODL. Problems faced include internet connectivity, inadequate learning devices and lack of skills during the implementation of full ODL. This study was conducted to assess perceptions and experiences (i.e. challenges, advantages and disadvantages) of ODL among Diploma in Pharmacy students. Data were obtained through a cross-sectional survey through online questionnaires. Questionnaires which consisted of demographic, perspectives and experiences towards ODL were distributed using WhatsApp and email. A total of 262 respondents (209 females and 53 males) completed the questionnaires. Majority of the students (94.3%) chose to study at home and used both mobile phones (92.4%) and laptops (96.2%) for ODL. Most students preferred ODL because of convenience (83.6%) whilst reduced concentration (80.9%) and poor internet connection (76.3%) were among the challenges encountered. Most frequently used digital platforms include UFUTURE (98.9%), Microsoft Teams (94.3%) and Google Classroom (89.7%). Likewise, live video conferencing (72.1%), pre-recorded videos (67.2%) and videos from online sources (59.5%) were among the most used type of delivery modes by lecturers. Our findings may help to strengthen the understanding of current ODL implementation and teaching processes. Results from this study will assist in improving various aspects of ODL to increase its effectiveness and efficiency for students’ learning.